Development and validation of the Environmental Confinement Stressors Scale (ECSS-20) - Santibáñez-Palma, J. Francisco; Ferrer-Urbina, Rodrigo; Sepúlveda-Páez, Geraldy; Bravo de la Fuente, Josefa; Alarcón-Castillo, Karina (Frontiers in Psychology, 2024)
The COVID-19 pandemic has generated a global crisis with severe consequences for public health. There have been negative impacts on people’s quality of life and mental health due to various stressors arising in this context, such as physical, social, economic, and psychological challenges. Noteworthy among these are the indirect effects of health measures, especially social distancing and confinement, which have significantly altered people’s daily lives and social activities, producing high levels of anxiety, depression, and stress. This study proposes developing and validating a cross-sectional scale called the “Environmental Stressors Scale (ECSS-20)” to address the need to measure the impact of environmental stressors during confinement. The scale, which has been validated following ethical and methodological guidelines, consists of four dimensions: economic stressors (EE), social activities (SA), habitability (H), and exposure to virtual media (EMV). A pilot study (n = 113) and a main study (n = 314) were applied. The results showed that the instrument has a reliable and valid structure, with satisfactory internal consistency and factorial validity. Likewise, gender invariance tests supported its suitability for its applicability to women and men. Overall, the ECSS-20 is a valuable instrument for assessing the impact of confinement and improving the understanding of people’s subjective experiences in this situation. Future research could further develop its applicability in different contexts and populations to better understand its usefulness and psychometric properties.